Analisis Peran Manajemen Rantai Pasok dalam Meningkatkan Efisiensi Distribusi Komoditas Cabai di Medan - Lokot Muda Harahap; Yose Maria Tumonggi Sibuea; Suci Ramadani; Dea Divella Tarigan; Kristiani Pakpahan; Nesah Sartika Harahap; Cindy Lastiur Silaen (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The distribution of red chili in Indonesia is often characterized by inefficiencies reflected in high marketing margins, low farmer’s share, and price volatility. These issues are closely related to the structure and management of the supply chain. This study aims to examine the role of supply chain management in improving the efficiency of red chili distribution by identifying key influencing factors and potential improvement strategies. The research employs a qualitative approach using a systematic literature review of national and international studies published between 2015 and 2024. A total of relevant articles were selected based on predefined inclusion criteria focusing on marketing efficiency, supply chain structure, and performance indicators. The findings indicate that inefficiency is primarily driven by long distribution channels involving multiple intermediaries, limited access to market information, weak farmer institutions, and inadequate post-harvest infrastructure. Empirical evidence shows that marketing margins range from 40-65%, while farmer’s share remains between 20-45%. Strategies such as shortening distribution channels, strengthening farmer organizations, improving price information systems, and developing cold chain infrastructure are found to significantly enhance distribution efficiency. These findings highlight the importance of integrated supply chain management in supporting a more efficient and equitable agricultural distribution system.